A photovoltaic cell integrated slot antenna for IoT applications - Ali, Ahmed; Park, Ikmo (2020 IEEE Wireless Power Transfer Conference, WPTC 2020, 2020)
A compact, low-profile photovoltaic cell integrated slot antenna is presented for Internet of Things (IoT) applications. The photovoltaic cell comprises a top metal grid, a GaAs layer, and a bottom metal contact. A slot is etched in the bottom metal contact of the photovoltaic cell; hence, the bottom metal contact is used as a ground plane for the antenna. The slot on the ground plane is excited by a 50-O microstrip line. The antenna has a size of 25 mm × 25 mm × 0.885 mm (0.48?o × 0.48?o × 0.017?o at 5.77 GHz). The antenna performance showed a -10 dB impedance bandwidth, from 5.60-5.94 GHz, a peak gain of 3.76 dBi, and radiation efficiency above 88% within the impedance bandwidth. The designed antenna can save a significant amount of real estate for IoT devices.
Keywords: Antenna performance; Ground planes; Impedance bandwidths; Internet of Things (IOT); IOT applications; Metal contacts; Radiation efficiency; Real estate; Compact antenna; Integrated antenna; IoT devices; Photovoltaic cell; Slot antenna